Climbing strategies of Taiwan climbers - Po-Hao Chen; An-Ching Chung; Hung-Chih Lin; Sheng-Zehn Yang (Botanical Studies, 2023)
Abstract Background The climbing strategies of lianas and herbaceous vines influence climber competition abilities and survival. The aim of this study was to investigate the climbing strategies of each plant species and observe their organs of origin. Results The results showed that all Taiwan climbers were approximately 555 species, accounting for 11% of the native flora. Among the 555 climbers, the twining stem type was the most common, with a total of 255 species (46%), the remaining climbing methods accounted for 300 species. Approximately twenty one climbing methods, including nine combination types, were exhibited, of which the most common type was the twining stem, followed by simple scrambling and twining tendrils. Most species of Fabaceae and Apocynaceae were twining stems in dextrorse, excluding Wisteriopsis reticulata and Alyxia taiwanensis, which were in sinistrorse. The prehensile branch of Fissistigma genus, Ventilago genus, and Dalbergia benthamii, originated from second-order or modified stems. In the simple scrambling type, some climbers were covered spines and prickles to attach the host, and the others were clinging to the supports or creeping on the ground without speculation. The hooks or grapnels of the genus Uncaria are derived from the branches, and a pair of curved hooks or a spine of Artabotrys hexapetalus are originated from the inflorescence to tightly attach to a host. The Piper genus use adhesive roots to climb their hosts. Among the genus Trichosanthes, only Trichosanthes homophylla exhibits a combination of twining modified shoots and adhesive roots. Gentianales includes four families with seven climbing mechanisms, while Fabales includes only Fabaceae, which presents six climbing methods. Conclusions The twining tendrils had nine organs of origin in Taiwan climber, that these opinions of originated organs might be available to the studies of convergent evolution. The data presented herein provide crucial basic information of the climber habits types and origin structures, which are available for terms standardization to improve field investigation. The terminologies would aid in the establishment of climber habits as commonly taxon-specific and the combination of two climber habits could be a characteristic of taxonomic value.